2008
DOI: 10.1128/ec.00230-08
|View full text |Cite
|
Sign up to set email alerts
|

Copper Distributed by Atx1 Is Available to Copper Amine Oxidase 1 in Schizosaccharomyces pombe

Abstract: Copper amine oxidases (CAOs) have been proposed to be involved in the metabolism of xenobiotic and biogenic amines. The requirement for copper is absolute for their activity. In the fission yeast Schizosaccharomyces pombe, cao1؉ and cao2 ؉ genes are predicted to encode members of the CAO family. While both genes are expressed in wild-type cells, we determined that the expression of only cao1 ؉ but not cao2 ؉ results in the production of an active enzyme. Site-directed mutagenesis identified three histidine res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Previous studies have shown that S. pombe possesses two copper-dependent amine oxidases, denoted Cao1 and Cao2 (25). It has been reported that Cao1 requires copper for its activity when expressed in mitotically growing cells (25).…”
Section: Mfc1 Expressed In Ctr4⌬ Ctr5⌬ Cells Proliferating In Mitosismentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that S. pombe possesses two copper-dependent amine oxidases, denoted Cao1 and Cao2 (25). It has been reported that Cao1 requires copper for its activity when expressed in mitotically growing cells (25).…”
Section: Mfc1 Expressed In Ctr4⌬ Ctr5⌬ Cells Proliferating In Mitosismentioning
confidence: 99%
“…It has been reported that Cao1 requires copper for its activity when expressed in mitotically growing cells (25). Because Cao1 molecular and cellular characterization has not yet been ascertained in meiosis, we have examined the subcellular location of an active Cao1-GFP fusion protein into an S. pombe h Ϫ /h ϩ cao1⌬/⌬ mutant strain that was induced to undergo azygotic meiosis.…”
Section: Mfc1 Expressed In Ctr4⌬ Ctr5⌬ Cells Proliferating In Mitosismentioning
confidence: 99%
See 2 more Smart Citations
“…Dr. Labbé's team has demonstrated that the metallochaperone Atx1 directly activates the copper amine oxidase Cao1 [19] . Although it has been shown that Atx1 specifically delivers copper to the copper ATPase Ccc2 in the secretory pathway [20,21] , Dr. Labbé's studies have described the first example of the ability of Atx1 to act as a copper carrier for a molecule other than Ccc2 [22] .…”
Section: Discovery Of Fep1 An Iron Sensor That Represses Iron Transpmentioning
confidence: 99%